Feeding-induced resistance to acute lethal sepsis is dependent on hepatic BMAL1 and FXR signalling - Sarah S. Geiger (Nature Portfolio, 2021)
Time of day influences immune responses and lethality in response to LPS, with survival greatest at the beginning compared to the end of the light cycle. Here the authors show that feeding, rather than light, controls time-of-day dependent LPS sensitivity through the liver clock and hepatic FXR signalling.